Assessing Customer Awareness of Sales Promotion Strategies at Bhat-Bhateni Supermarket in Nepal (Kaladarpan कलादर्पण, 2025)
This study investigates the role of consumer awareness in determining the effectiveness of sales promotion strategies employed by Bhat-Bhateni Supermarket in Nepal. From the theoretical perspectives of the consumer decision-making process, the research explains various ways in which demographic factors, communication, and the type of promotion influence purchase decisions. The study, in a descriptive research design with responses from 120 respondents, finds that the non-price-based promotions comprising loyalty programs and bonus packs will eventually ensure consumer loyalty for a long period rather than price-based promotion. It also points out that one must make use of digital platforms while targeting the tech-savvy consumer base among the youth along with demographic preferences by framing promotional strategy targeting their preferences. Results have pointed out the need for a balanced promotional mix that incorporates monetary and emotional incentives in pursuit of maximum short-term sales and long-term customer engagement.